CHARACTERIZATION OF CENTRIFUGAL CASTING METHOD FOR PULLEY MANUFACTURING USING VARIABLE ROTATIONAL SPEED - Wisnujati, Andika; Shomad, Muhammad Abdus (Media Mesin: Majalah Teknik Mesin, 2024)
Due to advancements in the industrial sector, aluminum is progressively gaining popularity as a material of choice in the field of engineering. A pulley is a component that functions as a link or transfers power or engine rotation to the load via the V-belt belt. This study aims to determine the characterization of aluminum material made by the centrifugal casting method from used brake shoes with rotational speed variables of 0 RPM, 100 RPM, and 200 RPM. The characterization of the casting results in this study was analyzed using the Brinell hardness test and the Charpy impact test. The results of the Brinell hardness test showed that aluminum castings for making pulleys with an additional 100 RPM die rotation speed had a Brinell hardness value of 53.22 BHN. The results of the impact test with the Charpy method showed that specimens with a mold rotation speed of 100 RPM had an impact value of 0.0135 kg.m/mm2. The results of this study concluded that variations in rotational speed of 100 RPM in the casting of pulleys made of used aluminum using the centrifugal casting method can produce products that have good toughness.